Identification SNP rs5219 KCNJ11 gene and blood glucose levels in type 2 diabetes mellitus patients at Moewardi Hospital Surakarta - Nur Aida; Rita Maliza; Imaniar Noor Faridah; Melinda Widianingrum; Dyah Aryani Perwitasari (Universitas Ahmad Dahlan, 2021)
Diabetes Mellitus (DM) is a metabolic disease that developed due to the pancreas does not sufficient to produce insulin or the body cannot effectively use the insulin it produces. Genetic factors have an essential role in the development of Type 2 Diabetes Mellitus (DMT2), which impaired insulin production by pancreatic Î² cells, insulin resistance, and action. The single nucleotide polymorphisms (SNP) in the KCNJ11 rs5219 affected the pancreatic Î² cell activity that can inhibit insulin release, thus causing a decrease in therapeutic effectiveness. The purpose of this study is to identify the SNP rs5219 of the KCNJ11 gene and measure patient blood sugar levels as the outcome of therapy. A cross-sectional study was conducted prospectively at Moewardi Hospital, Surakarta, involving 10 patients with DMT2 who received sulfonylureas therapy. DNA was isolated from the whole blood sample of DMT2 patients. PCR amplification was performed to amplify the KCNJ11 gene, and followed by PCR sequencing. The 2-H PP, FPG, and HbA1c parameters were measured as therapeutic outcomes. The results showed that the genotype frequencies (AA-AG-GG) were 10%, 50%, and 40%, while the allele frequency (A-G) in the sample was 35% and 65%. The uncontrolled values for 2H-PP on genotype (AA and AG + GG) were 10% and 20%; uncontrolled FPG on genotypes AA and AG + GG were 10% and 40%; and uncontrolled HbA1c on genotype AA and AG + GG were 10% and 80%. This study conclusion is the presence of the SNP rs5219 KCNJ11 gene with A>G base change in DMT2 patients who received sulfonylurea therapy.